2023
DOI: 10.3390/s23073605
|View full text |Cite
|
Sign up to set email alerts
|

BICM-ID Labeling-Based Recipient Identification in a Heterogeneous Network

Abstract: The concept of labeling-based recipient identification (LABRID) for bit-interleaved coded modulation with iterative decoding (BICM-ID) is revisited. LABRID allows addressing a message recipient station in a wireless network by using an individual labeling map without compromising error performance. This eliminates the need to use any byte of the data frame to carry the recipient address explicitly. In addition, the destination of the frame can be determined in parallel with a BICM-ID decoding procedure in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For this reason, the use of low-order modulations with hypercube labeling when E b /N 0 is much higher than considered here would require variable Θ. Although such a case is somewhat unrealistic, because a common practice when the channel state improves is to change the modulation order to a higher one, thereby increasing the data rate-in the light of previous contributions [4,5,10] it would also work with LABRID.…”
Section: Desired Threshold Valuementioning
confidence: 98%
See 1 more Smart Citation
“…For this reason, the use of low-order modulations with hypercube labeling when E b /N 0 is much higher than considered here would require variable Θ. Although such a case is somewhat unrealistic, because a common practice when the channel state improves is to change the modulation order to a higher one, thereby increasing the data rate-in the light of previous contributions [4,5,10] it would also work with LABRID.…”
Section: Desired Threshold Valuementioning
confidence: 98%
“…In Ref. [5], it has been shown that the LABRID receiver can effectively work in a "heterogeneous" environment, in which the signals of different modulation order are transmitted. In addition, the LABRID receiver demonstrated its capability of rejecting legacy BICM frames, in which the typical Gray labeling was used.…”
Section: Bicm-idmentioning
confidence: 99%